The third cohomology group classifies double central extensions - Rodelo, Diana (2008)
We characterise the double central extensions in a semi-abelian category in terms of commutator conditions. We prove that the third cohomology group H3(Z;A) of an object Z with coe cients in an abelian object A classi es the double central extensions of Z by A.